Increasing JSS female students' achievement in science through formative testing, feedback and remediation: a study in school effectiveness (2010)
The federal government of Nigeria emphasized the the importance of science and technology and had decided to have a ratio of science to liberal art in schools as 60:40. However, studetns' achievement (particularly females) in JSS integrated science is poor. Previous effort to increase students' performance has not yielded the desired result ; therefore, this study finds the effect of formative testing with feedback and remediation on students' achievement in the subject. This is a quasi-experimental design with a non-radomized pre-test and post-test control group (4X2) factorial design. Eight schools out of 25 in Ibadan North local government area were randomly selected and a total of 128 studetns participated in the study. Two instruments (intergrated science achievement test and treatment package) were employed to analyse the data. The study showed that a combination of formative testing, feedback and remediation used alongside teaching was an effective instructional strategy that could be used in reversing the trend of poor performacnce in junior secondary certificate examination in intergrated science by all students in general and female students in particular. It is therefore recommended that teaching + testing+ feedback+ remediation should be used in inteegrated science classes as this will improve all students' achivement in general and female students in particular